2009
DOI: 10.1007/s10265-009-0289-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dynamics and budget in a Zoysia japonica grassland, central Japan

Abstract: The ecosystem carbon budget was estimated in a Japanese Zoysia japonica grassland. The green biomass started to grow in May and peaked from mid-July to September. Seasonal variations in soil CO(2) flux and root respiration were mediated by changes in soil temperature. Annual soil CO(2) flux was 1,121.4 and 1,213.6 g C m(-2) and root respiration was 471.0 and 544.3 g C m(-2) in 2007 and 2008, respectively. The root respiration contribution to soil CO(2) flux ranged from 33% to 71%. During the growing season, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 63 publications
6
31
0
Order By: Relevance
“…These measurement data from Satomura et al (2006) could support the suggestion by Lee et al (2005). On the other hand, the seasonal changes in root respiration and root biomass at our grassland site (site Z) were reported by Dhital et al (2010). They found that the root respiration was highest in September, and suggested that this was caused by the increased root activity associated with higher below-ground biomass productivity.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…These measurement data from Satomura et al (2006) could support the suggestion by Lee et al (2005). On the other hand, the seasonal changes in root respiration and root biomass at our grassland site (site Z) were reported by Dhital et al (2010). They found that the root respiration was highest in September, and suggested that this was caused by the increased root activity associated with higher below-ground biomass productivity.…”
supporting
confidence: 85%
“…These sites were located within about 1 km of each other at about 1400 m above sea level. Site Q and site Z were described in detail by Ohtsuka et al (2005Ohtsuka et al ( , 2009 and Dhital et al (2010), respectively. We established a 20 m 6 20 m experimental area at each site.…”
Section: Site Descriptionmentioning
confidence: 99%
“…; Dhital et al . ; Toma et al . ) and comparable to those obtained in an intensively managed grassland without manure application (Shimizu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on soil respiration have been made in East Asia 14, 15, but there have been comparatively fewer research reports in the Loess plateau of China, especially in the eastern part of the plateau. As the second largest geographic unit in China, the plateau is characterized by its non‐uniform land cover.…”
Section: Introductionmentioning
confidence: 99%